Reformulation of the Legal Liability of Land Deed Officials for Defects in Authentic Deeds - Sudarwati, Dini Anggraini; Riyanto, Astim; Harlina, Indah (Jurnal Ilmu Hukum Kyadiren, 2026)
This study is motivated by the growing number of legal violations committed by Land Deed Officials (PPAT), encompassing administrative, ethical, and even criminal misconduct, as exemplified by the Magelang District Court Decision No. 56/Pid.B/2022/PN.MGG concerning the forgery of sale and mortgage deeds. The purpose of this research is to analyze the legal responsibility of PPATs in drafting authentic deeds that contain legal defects or elements of forgery and to examine the interrelation among administrative, ethical, and criminal violations within the framework of Indonesian positive law and the constitutional principle of social justice enshrined in the 1945 Constitution of the Republic of Indonesia. This research employs a normative juridical method using a statutory and case study approach. The findings reveal overlapping accountability mechanisms between ethical and criminal dimensions, as well as inadequate supervision of PPAT practices. It is therefore concluded that a reformulation of the sanction and supervision system for PPATs is necessary to ensure proportionality and alignment with the constitutional principle of social justice.